Impact of Moderate Sedation versus Monitored Anesthesia Care on Outcomes and Cost of Endobronchial Ultrasound Transbronchial Needle Aspiration - Boujaoude, Ziad; Arya, Rohan; Shrivastava, Aseem; Pratter, Melvin; Abouzgheib, Wissam (Pulmonary Medicine, 2019)
Background and Objectives. The ideal type of sedation for endobronchial ultrasound transbronchial needle aspiration (EBUS-TBNA) is not known. Two previous studies comparing the diagnostic yield between moderate sedation (MS) and deep sedation/general anesthesia (DS/GA) had provided conflicting results with one study clearly favoring the latter. No study had addressed cost. This is concerning for pulmonologists without routine access to anesthesia services. Our objective was to assess the impact of MS and Monitored Anesthesia Care (sedation administered and monitored by an anesthesiologist) on the outcomes and cost of EBUS-TBNA. Materials and Methods. We performed a retrospective review of prospectively collected data on consecutive EBUS-TBNA performed under two different types of sedation in a single academic center. A diagnostic TBNA was defined as an aspirate yielding any specific diagnosis or if subsequent surgery or follow-up of nondiagnostic/normal aspirates showed no pathology. Current Medicare time-based allowances were used for professional charges calculation. Results. There was no difference observed between MS and MAC in regards of the diagnostic yield (92.9% versus 91.9%), procedure duration, number, location, and size of lymph node (LN) sampled, but there were more passes per LN with MAC. The average charges were 74.30 USD for MS and 319.91 for MAC. There were more hypotensive and desaturations episodes with MAC but none required escalation of care. Conclusions. When performed under MS, EBUS-TBNA has similar diagnostic yield as under MAC but may be associated with less side effects. The difference in sedation cost is modest; however, an additional 245$ for each EBUS done under MAC would have significant cost implications on the health system. These findings are of critical importance for bronchoscopists without routine access to anesthesia services and for optimization of healthcare cost and resource utilization.